HAZARD INDEX and BUILDING VULNERABILITY ASSESEMENT IN PURBAYAN, KOTAGEDE, YOGYAKARTA - Muntafi, Yunalia (Eco Rekayasa: Jurnal Teknik Sipil, 2016)
There are so many natural disasters ever happened on many regions of Indonesia. The destructive impact of it has brought into focus the need for proper risk assessment. The great earthquake of May 26 2006 in Yogyakarta was responsible for the deaths of more than 5,000 people. The flood of 3 April 2008 in the same general area caused some devastation. The landslide of 22 March 2010 destroyed the Kaligesing-Yogya highway. Purbayan is one of villages in Kotagede district which is quite frequently hit by various kinds of disasters. Disasters such as these occurred in Purbayan need proper risk assessment studies to minimize the death toll and destruction. This study determined to get the hazard index of each kind of disaster that ever happened in Purbayan, Kotagede to find the biggest disaster risk of it. Analysis is performed by giving score to each kind of hazard, namely earthquake, flooding, landslide, strong wind, and fire uses risk assessment. This study was begunby observing and interviewing chief of neighborhood, some community leaders and local residents, then analyze it uses hazard identification analysis. Result in this study indicate that the hazard risk index of earthquake risk is 3,0, flooding is 2,46, fire is 1,58, and both landslide and strong wind is 1,0. This study shows that earthquake is the biggest disaster risk in Purbayan, Kotagede. The number of residential buildings that are vulnerable due to the earthquake as much as 36%, which is dominated by the building of type C, E, and F, which is the home using a combination of masonry wood frame, masonry without reinforcement, and a frame/wall of bamboo.Key words : disaster, earthquake, vulnerability assessment, hazard index